Female directorship and ethical corporate governance disclosure practices in highly patriarchal contexts - Tunyi Tunyi Abongeh (Journal of Business Research, 2023)
We examine whether and to what extent female directors impact on ethical CG disclosure practices in a highly patriarchal sub-Saharan African country—Nigeria. Using hand-collected data for 108 listed firms from 2011 to 2017 (756 firm-year observations) and employing a system GMM model to control for endogeneity, we show that female directorship is positively and significantly associated with ethical CG disclosures. Our evidence suggests that, even within patriarchal societies where women face negative preconceptions and stereotypes about their leadership capabilities, firms with female directors disclose higher ethical CG practices than firms without such representation. Furthermore, the effectiveness of female directors in influencing ethical CG practices is positively enhanced by foreign directors and institutional shareholders but weakened in larger boardrooms. We also evidence that in firm-level configuration of CG bundle, female directorship is a substitute mechanism for leadership duality, larger boards, non-executive and foreign directorship.